Fasting in Ramadan is safe for Individuals Suffering from Type 2 Diabetes Mellitus in Pakistan - Fatima Jehangir; Tooba Khan; Zainab Aziz; Arwa Giani; Tariq Adnan (ziauddin University, 2020)
Background: Whether diabetics should fast or not in Ramadan has been a controversial idea since long and the answer even more debatable. It confers safety measures to be known by the diabetics thoroughly, such as when to break the fast and what the hypoglycemic cut offs are. We aimed to determine hypoglycemic events and safety of Ramadan fasting among individuals with Type 2 Diabetes Mellitus (DM). Methods: This was an observational study enrolling diabetics who decided to fast in Ramadan, were aged >18 years, visited the primary health care center in Sikanderabad and Clifton clinic and gave consent to participate in the study. The exclusion criteria was Type 1 Diabetes Mellitus, Gestational diabetes, drug induced Diabetes and Maturity Onset Diabetes of the Young. A total of 103 participants were included in the study. Data was captured pre-Ramadan, during Ramadan and post-Ramadan in the year 2019. Multivariate Logistic regression was computed and chi-square taken for association of risk factors with hypoglycemia. p-value <0.05 was considered significant. Results: Mean HbA1c before Ramadan was 9.2%+2.1 and after Ramadan 7.7%+1.4 (p-value<0.05) showing a reduction of 1.5%. Mean weight of the patients before Ramadan was 68.3kg+1.6 and during Ramadan 64.8kg+1.4(p-value <0.00) showing a dip of 3.5 kg however mean weight 1 month after Ramadan was 66.5kg+14.9 depicting a rise again of 1.8kgs. Higher the risk category of American Heart Association, those who had hypoglycemic events before Ramadan and those on basal-bolus combination insulin had more hypoglycemic events (p-value <0.05). Conclusion: Fasting in Ramadan shows a major reduction in weight (3.5kg) as well as corrects hyperglycemia (1.5%). However, hypoglycemia was attributed to high risk patients only hence Ramadan fasting proved to be quite safe in individuals with Type 2 DM.